2018
DOI: 10.18176/jiaci.0209
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile of Lipid Transfer Protein Syndrome in a Mediterranean Area

Abstract: Palabras clave: Gadobutrol. Hipersensibilidad a contrastes de gadolinio. Reactividad cruzada entre contrastes de gadolinio. Medios de contraste paramagnéticos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 4 publications
2
11
0
2
Order By: Relevance
“…A study on nsLTP syndrome reported that in a group of 87 subjects sensitized to Pru p 3, 44% experienced anaphylaxis, 43% skin or oropharyngeal reactions, and 13% were asymptomatic. 103 It is generally accepted that nsLTP sensitization often occurs early in life. 104,105 Pru p 3 sensitization among children in a Spanish cohort was twice as high as that in adults.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…A study on nsLTP syndrome reported that in a group of 87 subjects sensitized to Pru p 3, 44% experienced anaphylaxis, 43% skin or oropharyngeal reactions, and 13% were asymptomatic. 103 It is generally accepted that nsLTP sensitization often occurs early in life. 104,105 Pru p 3 sensitization among children in a Spanish cohort was twice as high as that in adults.…”
Section: Epidemiologymentioning
confidence: 99%
“…Those sensitized to Pru p 3 may not always be symptomatic and the symptom severity may vary. A study on nsLTP syndrome reported that in a group of 87 subjects sensitized to Pru p 3, 44% experienced anaphylaxis, 43% skin or oropharyngeal reactions, and 13% were asymptomatic 103 . It is generally accepted that nsLTP sensitization often occurs early in life 104,105 .…”
Section: Epidemiologymentioning
confidence: 99%
“…Nonspecific lipid transfer proteins (nsLTPs) are present in multiple edible plants and are frequently responsible for food allergy (FA) in the Mediterranean area. NsLTPs are panallergens that have been associated with sensitization to multiple unrelated plant‐derived foods, inducing a complex clinical manifestation defined as LTP‐syndrome, whose management is considered a serious health problem . The peach nsLTP, Pru p 3, is the major allergen in the Mediterranean area .…”
Section: Introductionmentioning
confidence: 99%
“…To the editors, Lipid transfer protein (LTP) syndrome is the clinical situation present in patients with multiple sensitizations against LTP of different plant foods, due to the crossreactivity between these components. A significant number of anaphylactic reactions have been described in people affected, aggravated or triggered on many occasions by the presence of cofactors [1,2].…”
mentioning
confidence: 99%